ANALISIS IMPLEMENTASI KEUANGAN YAYASAN DALAM PROGRAM MAKAN BERGIZI GRATIS DAN DAMPAKNYA TERHADAP PEREKONOMIAN INDONESIA SERTA KESEJAHTERAAN PEKERJA - Rozi Pratama (PT. Samudra Solusi Profesional, 2026)
This study analyzes the implementation of foundation financial management in the Free Nutritious Meal Program and examines its impact on the Indonesian economy and workers’ welfare. A mixed-methods approach was employed by combining quantitative data from financial reports and surveys with qualitative data obtained through in-depth interviews with foundation administrators, workers, and local food suppliers. Descriptive statistical analysis was used to evaluate fund allocation, accountability, and financial efficiency, while content analysis and triangulation were applied to interpret the economic and social impacts of the program. The findings indicate that foundation financial management generally reflects transparency, accountability, and effective allocation of resources, particularly in the procurement of nutritious food ingredients and the absorption of local labor. The program contributes positively to economic circulation, employment opportunities, community income, and workers’ welfare through the involvement of local supply chains and community-based economic activities. In addition, the program supports improvements in nutritional quality and human capital development. Nevertheless, several small food vendors around schools experienced a decline in income due to shifting consumption patterns. Overall, the program demonstrates a significant contribution to social welfare, economic resilience, and sustainable community empowerment in Indonesia. This research offers a comprehensive perspective by integrating foundation financial governance, social policy, and economic impact analysis within a single analytical framework.